2017
DOI: 10.1159/000480117
|View full text |Cite
|
Sign up to set email alerts
|

Precision Medicine: From “Omics” to Economics towards Data-Driven Healthcare - Time for European Transformation

Abstract: There is room for improvement for optimally bringing the latest science to the patient while taking into account patient priorities such as quality of life. Too often, regulatory agencies, governments, and funding agencies do not stimulate the integration of research into care and vice versa. Re-engineering the drug development process is a priority, and healthcare systems are long due for transformation. On one hand, patients need efficient access to treatments, but despite precision oncology approaches, effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The integrative and expandable OP 4.1 platform concept can provide the registration and analysis of diverse results from diagnostics and therapy in real time and over time. As a result, a data infrastructure could be created, supporting the next major step into data-based individualized medicine with its personalized and customized therapies [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The integrative and expandable OP 4.1 platform concept can provide the registration and analysis of diverse results from diagnostics and therapy in real time and over time. As a result, a data infrastructure could be created, supporting the next major step into data-based individualized medicine with its personalized and customized therapies [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the drug-driven approach to bring new treatments to the market should ideally be balanced with a more patientfocused strategy, the former tends to dominate treatment development in oncology. As a result, many important aspects relating to the use of novel antitumor therapies in real-world settings are neglected throughout the process (Kempf et al, 2017;Lacombe et al, 2017;Lacombe et al, 2019b), as displayed in Table 1. For now, such clinically important and patient-centered questions are being addressed in a non-systematic and voluntary manner in the post-approval stage by non-commercial entities (Kempf et al, 2017), including academic research teams and notfor-profit organizations such as the European Organisation for Research and Treatment of Cancer (EORTC), which conducts independent international clinical trials in the field of oncology.…”
Section: Introductionmentioning
confidence: 99%
“…It is not intended to replace the current drug development trials; instead, it seeks to deliver results complementing those of the registrational studies as part of a streamlined process that bridges the gap between the first and second stage research (Kempf et al, 2017;Lacombe et al, 2019b). While no definitive methodological TABLE 1 | Overview of research concepts and questions that remain underrepresented in clinical cancer research today (Kempf et al, 2017;Lacombe et al, 2017;Lacombe et al, 2019b). The conclusions which may emerge from studies that explore such topics are highly relevant for clinical practice and are shown for a given treatment A.…”
Section: Introductionmentioning
confidence: 99%
“…It is not intended to replace the current drug development trials; instead, it seeks to deliver results complementing those of the registrational studies as part of a streamlined process that bridges the gap between the first and second stage research (Kempf et al, 2017;Lacombe et al, 2019b). While no definitive methodological (Kempf et al, 2017;Lacombe et al, 2017;Lacombe et al, 2019b). The conclusions which may emerge from studies that explore such topics are highly relevant for clinical practice and are shown for a given treatment A.…”
Section: Introductionmentioning
confidence: 99%